Inhibition of soluble TNFα prevents adverse atrial remodeling and atrial arrhythmia susceptibility induced in mice by endurance exercise. (April 2019) - Lakin, Robert; Polidovitch, Nazari; Yang, Sibao; Guzman, Camilo; Gao, Xiaodong; Wauchop, Marianne; Burns, Jacob; Izaddoustdar, Farzad; Backx, Peter H.
Abstract: Intense endurance exercise is linked to atrial fibrillation (AF). We established previously that interventions that simultaneously interfere with TNFα signaling, mediated via both the enzymatically liberated soluble and membrane-bound forms of TNFα, prevent atrial remodeling and AF vulnerability in exercised mice. To investigate which signaling modality underlies this protection, we treated exercised mice with XPRO®1595, a selective dominant-negative inhibitor of solTNFα. In male CD1 mice, 6 weeks of intense swim exercise induced reductions in heart rate, increased cardiac vagal tone, left ventricular (LV) dilation and enhanced LV function. By contrast, exercise induced hypertrophy, fibrosis, and increased inflammatory cell infiltrates in atria, and these changes were associated with increased AF susceptibility in isolated atria as well as mice, with and without parasympathetic nerve blockade. Although XPRO treatment had no effect on the beneficial physiological changes induced by exercise, it protected against adverse atrial changes as well as AF susceptibility. Our results establish that soluble TNFα is required for exercise-induced increases in AF vulnerability, which is linked to fibrosis, inflammation, and enlargement of the atria, but largely independent of changes in vagal tone. Highlights: Intense endurance exercise is associated with atrial fibrillation (AF) in mice. Exercise induced atrial hypertrophy, fibrosis, and inflammatory cell infiltrates. Inhibiting soluble TNFα prevented adverse atrial remodeling and AF vulnerability. HR reductions and physiological remodeling of the ventricles were unaffected. Soluble TNFα is required for increased AF vulnerability induced by intense exercise.